ANALISIS PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSET, RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PT. TELEKOMUNIKASI INDONESIA TBK - kurniawati, erna; muda, markus; Ningtyas, Juliana Dwi (LPPM Politeknik Saint Paul Sorong, 2022)
The purpose of this research are to know and understand the impact of Current Ratio, Debt to Equity, Return on Asset, and Return on Equity toward stock price at PT. Telekomunikasi Indonesia Tbk period 2017-2021. The method had be using in this research is quantitative approach. As for obtained the results of this research are regression test results of current ratio and return on equity known that the impacts are significant toward stock price. the results of regression test of debt to equity ratio and return on asset known that the impacts are not significant toward stock price. However, the other factor that had impacted the flu